Pengalaman Karyawan Gen-Z Di Banjarmasin Tentang Trust Dan Psychological Safety Dalam Mendukung Inovasi Kerja - Nadila Deryza (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2026)
This study explores the experiences of Generation Z employees in Banjarmasin regarding trust and psychological safety in fostering work innovation. The shifting workforce dynamics, dominated by Generation Z, necessitate that organizations—particularly in the retail sector—cultivate open and safe environments to encourage active participation. Employing a qualitative descriptive approach, data were gathered through in-depth interviews with retail employees in Banjarmasin and analyzed using thematic analysis. Findings reveal that open, supportive, and participatory leadership communication is vital for building trust. This trust establishes psychological safety, enabling employees to voice ideas or opinions without fear of negative repercussions. Consequently, such safety empowers Generation Z to innovate, especially regarding customer service quality and creative store layouts. These results confirm that trust and psychological safety are strategic assets for innovation. This research contributes theoretically to organizational communication studies and offers practical human resource management recommendations for managing younger generations.